2005
DOI: 10.1038/sj.emboj.7600686
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein hormone receptors: link between receptor homodimerization and negative cooperativity

Abstract: The monomeric model of rhodopsin-like G protein-coupled receptors (GPCRs) has progressively yielded the floor to the concept of GPCRs being oligo(di)mers, but the functional correlates of dimerization remain unclear. In this report, dimers of glycoprotein hormone receptors were demonstrated in living cells, with a combination of biophysical (bioluminescence resonance energy transfer and homogenous time resolved fluorescence/fluorescence resonance energy transfer), functional and biochemical approaches. Thyrotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
227
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 264 publications
(248 citation statements)
references
References 60 publications
(89 reference statements)
19
227
1
1
Order By: Relevance
“…As shown previously 26,36,37 , the rate of dissociation of radiolabelled TSH from the WT receptor is strongly accelerated in the presence of a large excess of cold hormone (Fig. 1g, black symbols), and this behaviour has been shown to reflect negative cooperativity of TSHr homomers 26 .…”
Section: Constitutively Active Tshr Mutants and Cooperativitysupporting
confidence: 77%
See 4 more Smart Citations
“…As shown previously 26,36,37 , the rate of dissociation of radiolabelled TSH from the WT receptor is strongly accelerated in the presence of a large excess of cold hormone (Fig. 1g, black symbols), and this behaviour has been shown to reflect negative cooperativity of TSHr homomers 26 .…”
Section: Constitutively Active Tshr Mutants and Cooperativitysupporting
confidence: 77%
“…On the basis of our assumption that negative cooperativity results from allosteric interactions between receptor protomers in a dimer or oligomer 26 , the observed reduction in allosteric behaviour of the mutants could be due to reduction of their ability to dimerize. Homogeneous time resolve fluorescence resonance energy transfer (HTRF) experiments demonstrated that constitutively active receptors are able to homomerize similarly to the WT receptor (Supplementary Fig.…”
Section: Constitutively Active Tshr Mutants and Cooperativitymentioning
confidence: 93%
See 3 more Smart Citations